Giant Otter (Pteronura brasiliensis) distribution and population status in Madre de Dios River basin, southeastern Peru - Mendoza, Joel Alexander (2017)
Population status and geographic distribution of the giant otter (Pteronura brasiliensis) from Madre de Dios Region (south-eastern Peru) of 2014 and 2015 periods are presented. Population census for each period were 128 individuals, grouped in 22 and 20 resident groups during 2014 and 2015 periods respectively. The Manu National Park (2.2 ind/10 km) and Bahuaja Sonene National Park (1.43 ind/10 km.) were the sectors with the greatest abundance of giant otters inside the natural protected areas (ANP), while, Las Piedras and Los Amigos rivers were the sectors, outside the ANP, with highest value of abundance: 0.5 and 0.43 ind/10 km respectively. The populations inside ANP show more stable and protected (17 resident groups), while outside ANP are more vulnerable, where we registered only five (2014) and two (2015) giant otter groups. Currently, the main threats for giant other populations from Madre de Dios and the cause of the environmental degradation of its habitats are the gold mining, agriculture and logging. This situation suggests the urgent need to establish a conservation program throughout the region, especially outside ANP.